Metabolic reprogramming in hepatocellular carcinoma: mechanisms of immune evasion and therapeutic implications - Bocheng Gao; Yan Lu; Xingyue Lai; Xi Xu; Shuhua Gou; Zhida Yang; Yanju Gong; Hong Yang (Frontiers in Immunology)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths worldwide, with limited treatment options for advanced stages. Metabolic reprogramming is a hallmark of cancer, enabling tumor cells to adapt to the harsh tumor microenvironment (TME) and evade immune surveillance. This review involves the role of metabolic reprogramming in HCC, focusing on the dysregulation of glucose, lipid, and amino acid metabolism, and its impact on immune evasion. Key metabolic pathways, such as the Warburg effect, fatty acid synthesis, and glutaminolysis, are discussed, along with their influence on tumor-associated macrophages (TAMs) and immune cell function. Targeting these metabolic alterations presents a promising therapeutic approach to enhance immunotherapy efficacy and improve HCC patient outcomes.